Similar effect of stem geometry on radiological changes with 2 types of cemented straight stem: The Müller stem and the Virtec stem compared in 711 hips - Clauss, Martin (Acta Orthop, 2016)
Background and purpose — There are 2 basic principles in cemented stem fixation: shape-closed and force-closed. We investigated 2 shape-closed straight stems, the Müller (MSS) and the Virtec (VSS), which differ only in geometrical cross section, to determine whether the difference in stem shape would affect the radiological results or long-term survival. Patients and methods — We included 711 hips (in 646 patients) that were operated on between July 1996 and July 2003. Patients randomly received either an MSS (n = 356) or a VSS (n = 355) and were followed prospectively. Radiographs taken at a follow-up of > 10 years were analyzed for osteolysis. Kaplan-Meier (KM) survival analysis was performed using various endpoints. We also performed Cox regression analysis to identify risk factors for aseptic loosening and osteolysis of the stem. Results — After 10 years, KM survival with “revision of any component for any reason” was 92% (95% CI: 88–95) for the MSS and 95% (CI: 92–97) for the VSS (p = 0.1). With “revision for aseptic loosening of the stem” as the endpoint, KM survival was 96% (CI: 9–98) for the MSS and 98% (CI: 97–100) for the VSS (p = 0.2). Cox regression showed that none of the risk factors analyzed were independent regarding aseptic loosening of the stem or regarding osteolysis. Interpretation — The MSS and the VSS showed excellent survival for aseptic loosening after 10 years. For the 2 different stem designs, we did not find any independent risk factors for aseptic loosening or development of osteolysis.